1972
DOI: 10.1002/1097-4679(197204)28:2<224::aid-jclp2270280232>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental desensitization of snake-avoidance after an instructional manipulation

Abstract: PROBLEM Leitenberg, et aE. ( 3 ) , and Oliveau, et al. ( 6 ) have reported experiments which, cumulatively, suggest that the beneficial effects of systematic desensitization depend on knowledge that one is "in therapy." Snake-avoidant Ss who experienced desensitization operations but who were unaware of the presumed therapeutic value of them did not benefit to the same degree as did Ss who knew that the operations were intended to be therapeutic. McGlynn, Reynolds and Linder (6) reported an experiment in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…To date, at least 11 studies have shown that credible expectancy modification procedures are capable of producing as great a reduction in fear as that produced by systematic desensitization (Gatchel, Hatch, Maynard, Turns, & Taunton-Blackwood, 1979; Kirsch & Henry, 1977; Kirsch et al, 1983; Lick, 1975; Marcia, Rubin, & Efran, 1969; McGlynn, 1971; McGlynn, Gaynor, & Puhr, 1972; McGlynn, Reynolds, & Linder, 1971; McReynolds et al, 1973; Slutsky & Allen, 1978; Tori & Worell, 1973). In addition, Gelder et al (1973) found an expectancy modification procedure to be as effective as desensitization in treating animal and tissue damage phobias.…”
Section: Expectancy and Fearmentioning
confidence: 99%
“…To date, at least 11 studies have shown that credible expectancy modification procedures are capable of producing as great a reduction in fear as that produced by systematic desensitization (Gatchel, Hatch, Maynard, Turns, & Taunton-Blackwood, 1979; Kirsch & Henry, 1977; Kirsch et al, 1983; Lick, 1975; Marcia, Rubin, & Efran, 1969; McGlynn, 1971; McGlynn, Gaynor, & Puhr, 1972; McGlynn, Reynolds, & Linder, 1971; McReynolds et al, 1973; Slutsky & Allen, 1978; Tori & Worell, 1973). In addition, Gelder et al (1973) found an expectancy modification procedure to be as effective as desensitization in treating animal and tissue damage phobias.…”
Section: Expectancy and Fearmentioning
confidence: 99%
“…Studies that have compared desensitization described as an effective therapy with desensitization disguised as an experimental or neutral procedure have led to inconsistent results. Whereas some investigations have shown that a therapeutic set results in better outcome than does a nontreatment set (Miller, 1972;Leitenberg et al, 1969;Oliveau, Agras, Leitenberg, Moore, & Wright, 1969), other investigations have shown no differences (Borkovec, 1972;McGlynn, 1971;McGlynn, Gaynor, & Puhr, 1972;McGlynn, Reynolds, & Linder, 1971a;Rosen, 1974).…”
Section: Expectancies For Change In Desensitizationmentioning
confidence: 99%
“…By way of contrast, the majority of the studies using the second type of expectancy manipulation have found significant effects on the outcome of desensitization. Specifically, six studies (Leitenberg, Agras, Barlow, & Oliveau, 1969;Miller, 1972;Oliveau, Agras, Leitenberg, Moore, & Wright, 1969;Persely & Leventhal, 1972;Rosen, 1974;Tori & Worell, 1973) have shown that therapeutic instructions produce significantly greater improvement than experimental instructions, whereas four studies (Borkovec, 1972;Mc-Glynn, 1971;McGlynn, Gaynor, & Puhr, 1972;McGlynn, Reynolds, & Linder, 1971a) have failed to show differences resulting from this expectancy manipulation. Lick and Bootzin (1975) have suggested that the latter four studies must be interpreted with caution, since only weak overall treatment effects were found in these studies.…”
Section: University Of Kansasmentioning
confidence: 99%